The Effect of Inflation, BI Rate, and Profit-Sharing Rate on NPF in Islamic Banks - Nisrina Qurrotul ’Aini; Shandrina Agustin Rahayu; Irwan Sutirman Wahdiat; Mardi Mardi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the effect of inflation, Bank Indonesia (BI) rate, and profit-sharing rate on non-performing financing (NPF) in Islamic commercial banks in Indonesia. Grounded in signaling theory, the research aims to identify how macroeconomic and internal banking factors influence the quality of Islamic banking assets. Using a quantitative approach, secondary data from eight Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) during the 2019–2023 period were analyzed. The study employed multiple linear regression analysis and classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests using SPSS version 25. The results indicate that inflation and BI rate have no significant effect on NPF due to the unique profit-sharing scheme in Islamic banks that adjusts to the profitability of customers' businesses. Conversely, the profit-sharing rate has a significant positive effect on NPF, suggesting that increases in the profit-sharing burden can heighten the risk of customer defaults. The findings underscore the distinct operational nature of Islamic banks and the necessity to monitor internal profit-sharing mechanisms more closely to manage financing risks effectively.